Adenosquamous carcinoma of the colon: a case report and review of the literature - Bravo-Taxa, Mercedes (2021)
Colorectal cancer is the third most frequently diagnosed cancer in both men and women. Adenocarcinoma is the most common pathologic subtype of colon cancer and constitutes 86% of all colon cancers. Nontheless, there are other less frequent sybtyes of colorectal carcinomas, such as adenosquamous carcinoma, an extremely rare form of colon cancer, but with worse prognosis and greater potential of metástasis. We present the case of a 68-year-old female presented with a two-month history of anemia, hematochezia and abdominal pain. The colonoscopic study presented a tumor in the ascending colon, which after surgical resection and pathological studies, turned out to be a primary colonoc adenosquamous carcinoma.